Overview of Elderly Risk Factors on Symptoms and Severity of Community-Acquired Pneumonia Using the PSI Score - Muren Dhianisa Dzakirah; Qomariah RS; Diniwati Mukhtar (Journal La Medihealtico, 2025)
Community-acquired pneumonia is a major cause of morbidity and mortality, particularly among the elderly. Age-related physiological changes, immune decline, and comorbidities may influence clinical manifestations and disease severity. Assessment of pneumonia severity using the Pneumonia Severity Index (PSI) is essential for appropriate clinical management. This study was an observational analytic study with a retrospective cross- sectional design using medical record data of elderly patients with community- acquired pneumonia at RSUD dr. Chasbullah Abdulmadjid, Bekasi, from May 2024 to April 2025. A total of 73 patients were selected using consecutive sampling. Data were analyzed using univariate and descriptive. Most patients were classified as elderly aged 60–74 years. The most common symptoms were cough and shortness of breath. Based on the PSI score, most patients had low to moderate pneumonia severity, while only a small proportion had severe pneumonia.Most patients were classified as elderly aged 60–74 years. The most common symptoms were cough and shortness of breath. Based on the PSI score, most patients had low to moderate pneumonia severity, while only a small proportion had severe pneumonia.